Synthesis of tungsten carbide nanoparticles in biochar matrix as a catalyst for dry reforming of methane to syngas. Issue 6 (27th June 2015) - Yan, Qiangu; Lu, Yongwu; To, Filip; Li, Yebo; Yu, Fei
<x xml:space="preserve">Abstract</x> Tungsten carbide (WC) nanoparticles were synthesized by carbothermal reduction (CR) of tungsten-promoted biochar.